A select library of the Nicene and Post-Nicene Fathers of the Christian church - Schaff, Philip; Wace, Henry; Gregory, Bishop of Nyssa (Edinburgh, Scotland T and T Clark, 1889)
Includes bibliographical references and indexes.
Vol. V contains writings of Gregory, Bishop of Nyssa
Keywords: Fathers of the church -- Primitive and early church -- ca 30-600